Sistem Hukum dalam Penyelesaian Perkara Perceraian pada Perkawinan Campuran di Indonesia - Utami, Putu Devi Yustisia; Sudiarawan, Kadek Agus; Mangku, Dewa Gede Sudika; Pratama, Alvyn Chaisar Perwira Nanggala (Universitas Negeri Malang, 2022)
This study aimed to analyze the legal system and the attitude of judges to resolve intermarriage divorce cases. This study used a normative juridical method with a statutory and conceptual approach. The study results showed that the judge determines the legal system in intermarriage divorce cases by evaluating the link points and collecting facts to find a relationship between the case and the possible legal system used based on the principles of international civil law. The attitude of judges in efforts to resolve mixed marriage divorce cases should not necessarily apply to Indonesian law. Judges should pay attention to foreign national parties' personal and national legal status based on Article 16 Algemeene Bepalingen van Wetgeving Voor Nederlands Indie.